Clay in situ resource utilization with Mars global simulant slurries for additive manufacturing and traditional shaping of unfired green bodies. (September 2020) - Karl, David; Duminy, Thomas; Lima, Pedro; Kamutzki, Franz; Gili, Albert; Zocca, Andrea; Günster, Jens; Gurlo, Aleksander
Abstract: The wet processing of regolith simulant for clay in situ resource utilization (ISRU) on Mars is presented. The two raw materials from the Mars global simulant family, one without clay (MGS-1) and one with clay - sodium montmorillonite smectite - (MGS-1C) were milled and mixed to produce a simulant with small particle size and reduced clay content (MGS-1C/8). All three simulants and the pure clay raw material were extensively characterized using XRF, synchrotron XRD, gas adsorption and gas pycnometry methods. In a straightforward processing approach, MGS-1C/8 was mixed with water and different dispersant approaches were investigated, all of which gave stable slurries. Particle size distribution, rheology, ion concentration, pH and electrical conductivity of these slurries were characterized. The slurry systems can easily be adapted to fit all typical ceramic shaping routes and here parts of varying complexity from slip casting, throwing on a potter's wheel and additive manufacturing, including material extrusion (robocasting) and binder jetting (powder bed 3D printing) were produced. The unique properties of the sodium montmorillonite clay, which is readily accessible in conjunction with magnesium sulfate on the Martian surface, acted as a natural nanosized binder and produced high strength green bodies (unfired ceramic body) with compressive strength from 3.3 to 7.5 MPa. The most elaborate additive manufacturing technique layerwise slurry deposition (LSD) produced water-resistant green bodies with a compressive strength of 30.8 ± 2.5 MPa by employing a polymeric binder, which is similar or higher than the strength of standard concrete. The unfired green bodies show sufficient strength to be used for remote habitat building on Mars using additive manufacturing without humans being present. Highlights: Clay ISRU using wet processing with slurries can produce stable green bodies. During dispersion, magnesium salt interacts with clay, facilitating cation exchange. Five different shaping methods have been used to form complex green bodies. Green body comp. strength is 3.3–7.5 MPa without and 30.8 MPa with binder. Unfired green bodies show sufficient compressive strength for habitat building.